Concurrent Tumor Treating Fields (TTFields) and Radiation Therapy for Newly Diagnosed Glioblastoma: A Prospective Safety and Feasibility Study - Bokstein, Felix; Blumenthal, Deborah; Limon, Dror; Harosh, Carmit Ben; Ram, Zvi; Grossman, Rachel (Frontiers in Oncology, 2020)
Background TTFields are a loco-regional, anti-mitotic treatment comprising low-intensity alternating electric fields. In the EF-14 study of newly diagnosed glioblastoma (ndGBM), TTFields in combination with temozolomide (TMZ) significantly improved survival versus TMZ alone. In preclinical studies TTFields had a radiosensitizing effect and increased the efficacy of radiation therapy (RT). This study prospectively evaluated the feasibility and safety of TTFields administered concurrently with RT and TMZ in ndGBM patients. Methods Patients with histologically confirmed ndGBM were treated with TTFields/RT/TMZ followed by adjuvant TMZ/TTFields. TTFields (200 kHz) were delivered for ≥18 hours/day with transducer arrays removed during RT delivery. RT was administered to the tumor bed in 30 fractions (total dose 60 Gy) combined with daily TMZ (75 mg/m2). In the adjuvant phase, patients received monthly TMZ (150–200 mg/m2 for 5 days) plus TTFields. Patients were followed for 24 months or until second disease progression. The primary outcome was safety of the combined therapies; secondary outcomes included progression-free survival (PFS) and overall survival (OS). Adverse events (AEs) were graded per CTCAE v4.0. Results Ten patients were enrolled at a single center between April and December 2017. Median age was 60.2 years, median Karnofsky Performance Score was 90.0, and 80% patients were male. Five (50%) patients had undergone tumor resection while the remainder had biopsy only. Eight patients experienced ≥1 RT treatment delay; delays were unrelated to TTFields treatment. All patients experienced ≥1 AE. Three patients suffered from serious AEs (urinary tract infection, confusional state, and decubitus ulcer) that were considered unrelated to TTFields. The most common AE was skin toxicity, reported in eight (80%) patients; all were of low severity (CTCAE grade 1–2) and were reported as related to TTFields treatment. Median PFS from enrollment was 8.9 months; median OS was not reached at the time of study closure. Conclusions Eighty percent of patients experienced grade 1–2 TTFields-related skin toxicity. No other TTFields-related toxicities were observed without an increase in RT- or TMZ-related toxicities as a result of combining TTFields with these therapies. Preliminary efficacy results are promising and warrant further investigation of concurrent TTFields/RT/TMZ treatment in ndGBM patients.